Clinical evaluation of children with celiac disease: A single-center experience - Yasin Sahin (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Background and objectives: The clinical findings of Celiac Disease (CD) change over time. Instead of classical symptoms such as diarrhea, growth retardation, abdominal bloating, atypical symptoms such as chronic constipation and abdominal pain may be the only sign of CD. In this study, we aimed to evaluate the clinical features of our patients with CD. Material and methods: This retrospective study was conducted between March 2017 and January 2019. 61 children with CD were included in the study. Local Ethics Committee approval was received. As an initial diagnostic test, tissue transglutaminase antibody (tTG) IgA test and total IgA test were analysed in all patients. Endomysial antibody (EMA) IgA test was analysed in patients with positive tTG IgA. If both celiac tests are detected as positive, gastroduodenoscopy was performed for definitive diagnosis of CD. Results: Of the 61 patients, 37 (60.6%) was female. The mean age of patients was 8.28±4.28 years. Tissue transglutaminase antibody (tTG) IgA test was positive in all patients, then endomysial antibody (EMA) IgA test was analysed in those patients. Endomysial antibody IgA test was also positive in all patients except three. The pathological results of our patients were Marsh 3a in 30 patients, Marsh 3b in 19 patients, and Marsh 3c in 12 patients. The positive family history of CD was found in the first degree relatives of 6 asymptomatic patients. Those patients were diagnosed with CD after celiac screening tests and endoscopic biopsy. Most of our patients had more than one symptom; 33 patients (54.1%) had classical symptoms such as failure to thrive and diarrhea, and 25 patients (40.9%) had non-classical symptoms.  Conclusion: The first degree relatives of celiac patients even if asymptomatic, and all patients with uncertain complaints and abnormal laboratory findings associated with CD should be evaluated for CD.